Elementy japońskich wierzeń i obrzędów w mandze Mieruko-chan. Dziewczyna, która widzi więcej Tomoki Izumiego - Ścibor Ratajczyk, Jakub (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The aim of the article is to reflect on religious themes in contemporary Japanese comics. The manga Mieruko-chan by Tomoki Izumi is analyzed. The themes include the Japanese tradition of horror, derived from folk beliefs, as well as Shintō and Buddhist rituals. The author draws attention to religion as an important element of creating cultural reality and its function that makes it more attractive.